Application of Bayesian Vector Autoregressive Model to the Analysis of J-curve in ECOWAS - Olubiyi, Ebenezer; Ologunwa, Oluyeni; Ogunro, Toluwalope (EuroEconomica, 2025)
Objectives: This study examines the existence and pattern of J-curve in ECOWAS region. Prior Work: From the theoretical standpoint, exchange rate devaluation leads to current account deterioration in the short run but leads to current account improvement in the long run. Empirical evidences do not unanimously support this assertion. Approach: A Bayesian vector autoregressive (BVAR) is utilized to forecast the pattern J-curve in 5 ECOWAS for data spanning 1990 to 2022. Results: J-curve does not exist in some countries. Specifically, Gambia experienced S-curve after 11 years while Togo experience trade surplus after 13 years. In Nigeria, J-curve exists in the short run but turned S-curve towards the long run. J-curve breaks down in Ghana and Cote d’Ivoire. International relative price influences the pattern of the J-curve, particularly in Francophone countries. Implication: Employing BVAR provides accurate, reliable and dependable results and researchers can benefit from utilizing it. The study also indicates that macroeconomic policy coordination in ECOWAS may not produce expected results for each country member. Value: This study if the first to employ BVAR in the analysis of J-curve in ECOWAS.